Relative bioavailability, food effect, and safety of the single-dose pharmacokinetics of omecamtiv mecarbil following administration of different modified-release formulations in healthy subjects - Palaparthy, Rameshraja (Int J Clin Pharmacol Ther, 2016)
Objective: Omecamtiv mecarbil is a novel small molecule that directly activates cardiac myosin and increases cardiac contractility without increasing cardiac myocyte intracellular calcium. This study evaluated the relative bioavailability, food effect, and safety of several modified-release (MR) formulations of omecamtiv mecarbil. Methods: This was a phase 1, randomized, open-label, 4-way crossover, incomplete block-design study evaluating 5 MR formulations of omecamtiv mecarbil vs. an immediate-release (IR) formulation. Materials: Healthy subjects were randomized to 1 of 30 possible sequences: within each sequence, subjects were assigned to receive a single 25-mg dose of 2 of the 6 possible formulations in the fasting and/or fed states. Results: 65 subjects were screened and enrolled; 5 were replacement subjects. Pharmacokinetic and safety data were analyzed from 62 and 63 subjects in the fasting and fed states, respectively. Compared with the IR formulation, median t(max) was longer (0.5 vs. 2 – 10 hours), and mean C(max) was lower for all 5 MR formulations (262 vs. 34 – 78 ng/mL); t(1/2,z) was similar (18 – 21 hours). The relative bioavailability was high (> 75%) for three MR formulations but lower (< 65%) for the other two. Overall, the effect of food on omecamtiv mecarbil pharmacokinetics was minimal for four of the MR formulations. The pharmacokinetics of the inactive metabolites M3 and M4 were similar across all formulations. Conclusions: The relative bioavailability of omecamtiv mecarbil was high (> 75%) for 3 of the five MR formulations. Food had a marginal, nonclinically meaningful effect on the pharmacokinetics of the MR formulations of omecamtiv mecarbil.